Pengembangan Media Pembelajaran Berbasis Android Menggunakan MIT App Inventor Pada Mata Pelajaran Administrasi Perpajakan Kelas Akuntansi SMK Negeri di Surabaya - Sakinah, Iftitahus; Susanti, Susanti (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
Technological development in the Society 5.0 era requires the integration of digital media in the learning process. However, in practice, Tax Administration learning at SMK Negeri Surabaya is still mostly lecture-based and uses conventional media, so students don't really get the hang of PPN and PPnBM stuff. This research is intended to develop Android-based learning media utilizing MIT App Inventor that is contextual and tailored to students' needs. The method of research utilizes the ADDIE development model through the stages of analysis, design, development, implementation, and evaluation. The final product is an Android application with features including Materials, Quizzes, Tax Calculator, and Developer Profile. Expert validation of the content yielded a suitability score of 86.25%, and expert validation of the media yielded a score of 93.33% (category: highly suitable). A limited trial involving 20 students resulted in a positive response rate of 98.21%, showing that the media is user-friendly, engaging, and aids in understanding tax concepts. Based on these results, this media is effective and suitable for utilization in supporting Tax Administration education at vocational high schools.